Perancangan Emergency Response Plan di PT E-T-A Indonesia - Glorius, Yoel; Panjaitan, Togar W S (Jurnal Titra, 2013)
PT E-T-A is a German based company and has designed several emergency response systems as its major business. The company would like to plan a complete emergency response system. This plan is executed by adding the active protection system, rescuing people procedures, and developing rescuerer team. In the new emergency response system design, we added an active protection system, consisting of smoke detector, manual call point, fire alarm. Additionally, we also relocated some APARâs locations which carry out the government regulation: PermakerNo.04/Men/1980 in 2009. Moreover, we added an assembly point, evacuation route, and rescuerer team.